Multicenter continuum-distorted-wave eikonal-initial-state description of the electron-impact ionization of aligned H2 molecules - Acebal, Emiliano (2020)
In this work, the multicenter continuum-distorted-wave (CDW) eikonal-initial-state (EIS) model is introduced. In contrast to previously reported CDW EIS analyses for electron-molecule collisions, in which the ionized electron interacted with the molecular ion via a one-center effective potential, the multicenter nature of the molecular ion is explicitly taken into account. Results obtained for electron-impact ionization of oriented H2 molecules at the fully differential level are presented and contrasted with recent experimental data and reported theoretical calculations obtained with the time-dependent close-coupling method. The present results suggest that this simple molecule still represents a challenging target from a theoretical point of view and that many aspects of the ionization process at the fully differential level remain to be understood.